2004
DOI: 10.1002/pola.20529
|View full text |Cite
|
Sign up to set email alerts
|

Photocuring kinetics of UV‐initiated free‐radical photopolymerizations with and without silica nanoparticles

Abstract: We used photodifferential scanning calorimetry to investigate the photocuring kinetics of UV-initiated free-radical photopolymerizations of acrylate systems with and without silica nanoparticles. Two kinetics parameters-the rate constant (k) and the order of the initiation reaction (m)-were determined for hybrid organicinorganic nanocomposite systems containing different amounts of added silica nanoparticles (0 -20 wt %) and at different isothermal temperatures (30 -100°C) using an autocatalytic kinetics model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
102
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(104 citation statements)
references
References 32 publications
2
102
0
Order By: Relevance
“…These were already observed for other acrylate systems, including HBP, 22 and for silica nanocomposites. 19 At the beginning of the reaction, a sharp increase in the rate of polymerization was evident, which corresponded to gelation or autoacceleration. Due to the increasing viscosity, the mobility of the long-chain radical species was reduced; hence, two radical species were less likely to approach each other and recombine.…”
Section: Photocalorimetry Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…These were already observed for other acrylate systems, including HBP, 22 and for silica nanocomposites. 19 At the beginning of the reaction, a sharp increase in the rate of polymerization was evident, which corresponded to gelation or autoacceleration. Due to the increasing viscosity, the mobility of the long-chain radical species was reduced; hence, two radical species were less likely to approach each other and recombine.…”
Section: Photocalorimetry Analysismentioning
confidence: 99%
“…[16][17][18][19] Harsch et al 20 found a reduction in conversion of epoxy resin when silica filler was added. In contrast, Cho et al 19 showed that formulations containing silica nanoparticles gave higher ultimate conversion. The latter result would most likely favor shrinkage and stress.…”
Section: Introductionmentioning
confidence: 99%
“…This technique is capable of providing photopolymerization kinetics data in which the measured heat flow can be converted directly to the ultimate percentage conversion and polymerization rate for a given formulation, with the data obtained reflecting the overall curing reaction of the sample. However, it should be noted that the cure kinetics data obtained in this study are essentially empirical and do not provide any mechanistic insight [10][11][12].…”
Section: Resultsmentioning
confidence: 99%
“…Aaccurate kinetics analyses yield quantitative data on the photocuring behaviors of PFPE-based systems for designing new types of MEMS devices [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…[24][25] On the other hand, in some studies, an optimum loading of silica nanoparticles has been reported in which the polymerization rate reaches the maximum value. [26][27][28][29] In these studies, silica nanoparticles can improve the mobility and diffusion of propagating radicals, which lead to increase in the rate of polymerization. In this work, the reduction of polymerization rate at higher amount of particles has been attributed to less system stability due to the formation of aggregates.…”
Section: Polymerization Kineticsmentioning
confidence: 99%